How to Become an Effective Course Director - Newton, Bruce W.; Menna, Jay H.; Tank, Patrick W. (Springer New York : Imprint: Springer, 2009)
If you think you know what students expect from a course director - think again. The surprising results show that students desire qualities in a course director that are different from what course directors think students want. This book gives advice on how to manage the differences in expectations between students and veteran or beginning course directors. The authors learned the hard way and bring over 60 years of collective course director and academic dean experience to bear on topics such as "Living with our Differences, Course Organization, Responding to Student Issues, Measuring Course Effectiveness and Pitfalls to Avoid". Written from the perspective of medical education, this book is germane for anyone who directs a health-related professions or college-level course. This is an essential, concise survival guide for anyone who desires to be a course director or, more likely, who has been thrust into the position and needs a primer. Get the upper hand on the students (and the administration) right from the start by applying the advice given in this book.